Duties and Functions of the Prosecutor's Office in the Civil and State Administration Sector (Case Study at the Central Kalimantan High Prosecutor's Office): Tugas dan Fungsi Kejaksaan di Bidang Perdata dan Tata Usaha Negara (Studi Kasus di Kejaksaan Tinggi Kalimantan Tengah) - Nitami Nurullita; Annisa Rahmanita; Anisa (PT Syamilah Literasi Islami, 2024)
This study examines the roles and responsibilities of the Indonesian Attorney General's Office in the fields of civil and administrative law, with a specific focus on the Central Kalimantan Prosecutor's Office. The research aims to clarify the duties of the Attorney General's Office as the state's attorney in representing the government and public interest in civil and administrative cases. Utilizing a normative juridical and empirical approach, the study analyzes both primary and secondary data, including interviews with legal experts. Findings indicate that the Attorney General's Office holds extensive authority in civil and administrative matters, including legal assistance, legal opinions, and mediation services, while also facing challenges such as bureaucratic obstacles and limited resources. The conclusion emphasizes the necessity of strengthening the institution's resources to enhance its role in civil law and state administration, thereby aiding in the recovery of state assets.